1992
DOI: 10.1104/pp.98.2.687
|View full text |Cite
|
Sign up to set email alerts
|

Complementary DNA Cloning of Poplar Bark Storage Protein and Control of Its Expression by Photoperiod

Abstract: Bark storage proteins accumulate in the bark of many woody plants during autumn and winter. In poplar (Populus de/toides Bartr. ex Marsh), the accumulation of the 32-kilodalton bark storage protein is controlled by photoperiod. We have isolated a full-length cDNA encoding for the poplar 32-kilodalton bark storage protein and determined its nucleotide sequence. The derived amino acid sequence shows that poplar bark storage protein is rich in serine, leucine, phenylalanine, and lysine. Poplar bark storage protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 27 publications
2
70
1
Order By: Relevance
“…During autumn this protein accumulates in protein storage vacuoles of the inner bark parenchyma (Wetzel et al, 1989a(Wetzel et al, , 1989b and xylem ray cells (Sauter et al, 1989). Accumulation of BSP and BSP mRNA is associated with short days (Coleman et al, 1991(Coleman et al, , 1992Langheinrich and Tischner, 1991) and may also be related to nitrogen availability (Wetzel and Greenwood, 1991;van Cleve and Apel, 1993). Degradation of poplar BSP and nitrogen remobilization appear to be related to sink demands from active bud growth .…”
mentioning
confidence: 99%
“…During autumn this protein accumulates in protein storage vacuoles of the inner bark parenchyma (Wetzel et al, 1989a(Wetzel et al, , 1989b and xylem ray cells (Sauter et al, 1989). Accumulation of BSP and BSP mRNA is associated with short days (Coleman et al, 1991(Coleman et al, , 1992Langheinrich and Tischner, 1991) and may also be related to nitrogen availability (Wetzel and Greenwood, 1991;van Cleve and Apel, 1993). Degradation of poplar BSP and nitrogen remobilization appear to be related to sink demands from active bud growth .…”
mentioning
confidence: 99%
“…Although VSPs have been identified in the vegetative organs of several temperate trees (van Cleve et al 1988;Wetzel et al 1989;Clausen and Apel 1991;Langheinrich and Tischner 1991;Stepien and Martin 1992;Coleman 2001a, 2001b), their seasonal fluctuation was assumed to be similar to that of the other so-called stored nitrogen compounds as above (Wetzel et al 1989). On the basis of this assumption, external factors such as nitrogen application, low temperature and short days play an important role in regulating VSP accumulation (Clausen and Apel 1991;Langheinrich and Tischner 1991;Coleman et al 1991Coleman et al , 1992Coleman and Chen 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The external factors, such as low temperature and short days, have been emphasized as key signals in inducing VSP accumulation in trees (Causen and Apel 1991;Langheinrich and Tischner 1991;Coleman et al 1991Coleman et al , 1992Coleman and Chen 1993). Recently, we found that the seasonal fluctuation of VSPs was very similar between the tropical tree S. macrophylla and the temperate tree Populus canadensis, suggesting that this seasonal fluctuation pattern in the whole tree might be an important mechanism by which the trees regulated their growth (Tian et al 2003(Tian et al , 2005.…”
mentioning
confidence: 88%
“…The accumulation of poplar BSP is associated with short days (Coleman et al, 1991). SD accumulation of poplar BSP is also correlated with a large increase in the steady-state levels of BSP mRNA (Coleman et al, 1992). DNA gel blot analysis suggests that poplar BSP is encoded by a small multigene family.…”
mentioning
confidence: 91%
“…A genomic library was prepared in the vector XGem-11 (Promega, Madison, WI) and screened at low stringency (approximately 25OC below Tm) using a poplar BSP cDNA (Coleman et al, 1992). Twelve positive clones were identified and rescreened with different regions of the BSP cDNA at high stringency (approximately 5OC below Tm).…”
mentioning
confidence: 99%